PEMANFAATAN TANAH DI ATAS HAK PENGELOLAAN ANTARA REGULASI DAN IMPLEMENTASI - Silviana, Ana (Diponegoro Private Law Review, 2017)
Right of Management (HPL) is part of the state right to control the land and part of the rights delegates to the HPL holders. In order to carry out the construction HPL holders may grant land rights on HPL with a land use agreement (SPT). In practice, however, there are often legal issues related to the granting of land rights over HPL, especially HPL requested on land that already belongs to state owned company (BUMN / BUMD), or also Local Government to be converted into commercial activities. This paper will examine the legal problems arising from land use on HPL. The method used in this paper is a doctrinal / legal approach, where the law is conceived as a legislation. The result of HPL analysis is not the right to land as stipulated in the LoGA, in the application of land above the HPL the extension of their rights to rights holders on HPL may be given priority after obtaining approval from HPL holders. Keywords:  Right of Management, Land Use Agreement, Local Government Asset